Quality of Life and Its Associated Factors in Patients After Esophagectomy at a Single National Referral Center - Sirirui, Dogma H.; Putranto, Agi S (The New Ropanasuri Journal of Surgery, 2022)
Introduction. Esophagectomy is the standard surgical treatment for resectable esophageal cancer patients. However, the success rate for this procedure was about 25–35% and was associated with a severe risk of postoperative complications. In addition, patients after esophagectomy have decreased their quality of life (QOL), but no research has been done in Indonesia. Therefore, this study was conducted to determine the quality of life after esophagectomy in Indonesia based on the patient population at Dr. Cipto Mangunkusumo General Hospital (CMGH). Method. A retrospective study was conducted using quality–of–life instruments issued by the European Organization for Research and Treatment of Cancer (EORTC). It consists of the module for esophageal cancer EORTC–QLQ–OES18 and the core questionnaire C30. Subjects were patients after esophagectomy in 2015–2021 at CMGH. Results. About 35 subjects underwent esophagectomy and followed by reconstruction, which comprised 62.9% males and 37.1% females. The mean age was 43.8 + 13.1 years. All subjects' median global health was 83.3 (IQR: 25.0). The overall functional scale question item with the lowest score was cognitive functioning (CF) 66.7 (IQR: 50.0). Meanwhile, based on the question items on the overall symptom scale, the worst scores were nausea and vomiting (NV) 16.7 (IQR: 50.0), pain (PA) 16.7 (IQR: 33.3), dysphagia (OESDYS) 33.3 (IQR: 33.3), eating (OESEAT) 34.5 (IQR: 23.9), choking (OESCH) 33.3 (IQR: 33.3), and coughing (OESCO) 33.3 (IQR: 33.3). Conclusion. The overall QOL after esophagectomy at CMGH based on the EORTC–QLQ–C30 and OES18 questionnaires was good. However, prognostic factors associated with decreased quality of life should be better educated to patients and prepared well before the esophagectomy procedure, thus maximizing quality of life after esophagectomy.